Industrial visual inspection of lime granules by neural networks - Carvalho, P. (1998)
Lime granule quality inspection is an important task in the pulp and paper industry. In this paper a new method, build-up on a neural network and a path search method, is introduced for lime granule automatic visual inspection. Several correction steps to Landau's method are also introduced.